Developing inland China: Do heterogeneous coastal foreign direct investments and exports help? - Puman Ouyang; Shunli Yao (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2013)
By applying panel estimation models to Chinese provincial level data for 1993-2008, this paper examine the impacts of China's coastal foreign direct investment (FDI) and exports on its inland regions. The results show that coastal FDI has overall positive interregional impacts, while coastal exports do not. Cooperative joint ventures generate positive impacts, but little impact is produced by wholly foreign-funded enterprises. In the case of equity joint ventures, there may even be negative impacts. The interregional impacts do not exhibit any differences across FDI origins or exporters' ownership status. The authors attribute these findings to the protectionist behaviour of state-owned enterprises participating in equity joint ventures as well as to the prevalence of processing exports.
Keywords: F23; O33; R11; R12; 330; Foreign direct investment; exports; interregional spillovers; China